Shared Fate and Entrepreneurial Collective Action in the U.S. Wood Pellet Market - Hiatt, Shon R.; Park, Sangchan (Organization Science, 2022)
Although studies underscore the importance of creating a coherent collective identity in order to legitimate a new market category, strategy and entrepreneurship research is divided on whether and to what degree an entrepreneur will engage in collective action to promote the identity. To reconcile the inconsistency, we introduce the concept of entrepreneurial shared fate—the belief of a focal venture that it and its competitors are bound together by a sense of belongingness and equally experience similar consequences—and explore how external threats can influence the degree of shared fate. We conceptually distinguish between communal and individual threats and propose that communal threats will increase, whereas individual threats will decrease, shared fate. We also explore boundary conditions that strengthen and weaken the main effects of perceived communal and individual threats on collective identity promotion. Empirically, we examine venture identity framing in response to forest-conservation activism in the U.S. wood pellet market. Implications for research on new market categories, collective identity, optimal distinctiveness, and forest management are discussed.